The Effect of the Role of Social Partners on the Performance of State Corporations in Kenya - Nzioki, Susan; Gachunga, H. G. (International Journal of Advances in Management and Economics, 2013)
The study sought to establish the effect of the role of social partners on the performance of state corporations in Kenya. Methodology: Data was obtained through a descriptive design involving 279 employees both unionized and non-unionized of state corporations in Nairobi County. A structured questionnaire with likert scale questions was used to collect data from the selected subjects of the study. Interviews were also conducted with human resource managers/ employee relations officers, shop floor union officials, officers of the Ministry of Labour, officers of Federation of Kenya Employers (FKE), officers of Central Organizations of Trade Unions, Kenya (COTU). The study was supported by the Dunlop’s systems model. The output of the system’s approach are rules. The rules govern the duties and performance expected of employees and employers and the procedures set by the state to govern the performance of the roles. Finding: The study found that employers and trade unions performed their duties adequately, but they did not embrace the publicity and acquaintance of Industrial Relations Charter which prescribed the roles to be played by the partners. The Ministry as the third party initiated, elaborated and implemented labour policy and law. The Ministry however had human resource constraints, in terms of numbers and competence. It also suffered infrastructural incapacity and inadequate budgetary allocation. However the partners' roles positively influenced the performance of state corporations. Limitation: The study was conducted in a few state corporations and therefore cannot be generalized in the private sector in the country. Practical Implications: Provides evidence on the roles of the social partners and how they have affected the performance of state corporations. It provides recommendations on what the social actors can do to improve the performance of their roles and consequently enhance harmonious industrial relations to improve on performance. Originality: This is the first study of this nature conducted in Nairobi County in Kenya focusing on the effects of the social partners' roles on the performance of state corporations.
Keywords: Kenya, Nairobi County, Social Partners, State Corporations.